2021
DOI: 10.1111/codi.15946
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary patterns of chromosomal instability and mismatch repair deficiency in proximal and distal colorectal cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…Interestingly, our analysis of Boolean implication networks revealed a larger contribution of genes specifically present in Boolean implication networks in the case of COAD bearing GAIN-Chr20. Our result in COAD is in agreement with the observation that GAIN-Chr20 is a frequent and early-appearing abnormality in colon cancer [ 35 38 ], thus suggesting that GAIN-Chr20 exerts a stronger cancer driving force in the context of colon cancer in comparison to other cancer types, such as STAD, BLCA and CESC. Indeed, several research groups have reported the importance of Chr20 amplification in colon cancer, and attributed such effect to the location of multiple oncogenes such as BCL2L1, AURKA, TPX2, and SRC on this chromosome [ 39 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, our analysis of Boolean implication networks revealed a larger contribution of genes specifically present in Boolean implication networks in the case of COAD bearing GAIN-Chr20. Our result in COAD is in agreement with the observation that GAIN-Chr20 is a frequent and early-appearing abnormality in colon cancer [ 35 38 ], thus suggesting that GAIN-Chr20 exerts a stronger cancer driving force in the context of colon cancer in comparison to other cancer types, such as STAD, BLCA and CESC. Indeed, several research groups have reported the importance of Chr20 amplification in colon cancer, and attributed such effect to the location of multiple oncogenes such as BCL2L1, AURKA, TPX2, and SRC on this chromosome [ 39 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…183, unpublished data). Gain for chromosomal region 13q11-q34 obviously represents an early event, since it was present in primary CRC and all metastatic sites (Golas et al 2022 ). Accordingly, this aberration had been described at the transition from adenoma to primary CRC (Hermsen et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gutenberg et al had identified 20q as the most frequently occurring copy number change in 11 patients with brain metastases (Gutenberg et al 2010 ). Additionally, this gain had often been detected in CRC primary tumors and been described as an early event in CRC tumor progress (Golas et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that aberrant function of proteins involved in chromosome separation could induce aneuploidy which was found in many types of cancer (6,7). Aneuploidy is usually caused by an abnormal number and size of the centrosome, may accelerate tumorigenesis and carcinogenesis by causing chromosomes to separate unequally during mitosis (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%